Evidence for differential care in Down syndrome screening based on maternal origin: a population based survey in France. (20th October 2021) - Anselem, O; Saurel-Cubizolles, MJ; Khoshnood, B; Sauvegrain, P; Bertille, N; Azria, E
Abstract: Background: Previous studies showed disparities in prenatal screening for Down syndrome according to socio-economic status and maternal place of birth. Thus, it remains uncertain that those disparities are related to access difficulties or lack of information offered to women. Our objective was to assess the opportunity for informed choice regarding Down syndrome screening according to maternal place of birth. Methods: Data were based on French national perinatal surveys of 2010 and 2016. These surveys include several questions relative to Down syndrome screening, such as measurement of nuchal translucency and realization of maternal serum screening. We considered that women had the opportunity for choice in case of realization or refusal of prenatal screening, or realization of amniocentesis or chorionic villous sampling. We considered that women had no opportunity for choice in case of ignorance of the realization of the tests, or if the screening has not been performed because not proposed, late prenatal follow-up, or another reason or unknown reason. We used multinomial logistic regression models to assess the association between the use of the tests and women country of birth. Results: The proportion of women undergoing measurement of nuchal translucency or maternal serum screening was higher in women born in France than women born in another country. After adjustment on the year of the survey, maternal age, parity, education level and type of maternity, and after exclusion of women without adequate prenatal follow-up, the opportunity for making an informed choice for Down syndrome screening was higher for women born in France than women born in another European country (ORa 2.36; 95%CI, 1.8-3.0), in Maghreb (ORa 4.01; 95%CI, 3.4-4.8) or in another African country (ORa 3.52(2.8-4.3). Conclusions: Disparities in the use of Down syndrome screening according to women place of birth are almost partly related to differences in the opportunity of an informed choice.